Pre-operative Functional Cardiovascular Reserve Is Associated with Acute Kidney Injury after Intervention. (May 2017) - Saratzis, A.; Shakespeare, J.; Jones, O.; Bown, M.J.; Mahmood, A.; Imray, C.H.E.
Abstract : Background: Acute kidney injury (AKI) is a common complication after endovascular intervention, associated with poor short and long-term outcomes. However, the mechanisms underlying AKI development remain poorly understood. The impact of pre-existing cardiovascular disease and low cardiovascular reserve (CVR) in AKI is unclear; it remains unknown whether AKI is primarily related to pre-existing comorbidity or to procedural parameters. The association between CVR and AKI after EVAR was therefore assessed. Methods: This is a case control study. From a database of 484 patients, 292 undergoing elective endovascular aneurysm repair (EVAR) of an infrarenal abdominal aortic aneurysm (AAA) in two tertiary centres were included. Of these, 73 patients who had developed AKI after EVAR were case matched, based on pre-operative estimated glomerular filtration rate (eGFR; within 5 mL/min/1.73 m 2 ) and age, with patients who had not developed AKI. Cardiopulmonary exercise testing (CPET) was used to assess CVR using the anaerobic threshold (AT). Development of AKI was defined using the Kidney Disease Improving Outcomes (KDIGO) guidance. Associations between CVR (based on AT levels) and AKI development were then analysed. Results: Pre-operative AT levels were significantly different between those who did and did not develop AKI (12.1±2.9 SD vs. 14.8±3.0 mL/min/kg, p < .001). In multivariate analysis, a higher level of AT (per 1 mL/min/kg) was associated with a lower odds ratio (OR) of 0.72 (95% CI, 0.63–0.82, p < .001), relative to AKI development. A pre-operative AT level of < 11 mL/min/kg was associated with post-operative AKI development in adjusted analysis, with an OR of 7.8 (95% CI, 3.75–16.51, p < .001). The area under the curve (receiver operating characteristic) for AT as a predictor of post-operative AKI was 0.81 (standard error, 0.06, 95% CI, 0.69–0.93, p < .001). Conclusions: Poor CVR was strongly associated with the development of AKI. This provides pathophysiological insights into the mechanisms underlying AKI.